JWST Observations of the Enigmatic Y-Dwarf WISE 1828+2650. I. Limits to a Binary Companion - Matthew De Furio; Ben Lew; Charles Beichman; Thomas Roellig; Geoffrey Bryden; David Ciardi; Michael Meyer; Marcia Rieke; Alexandra Greenbaum; Jarron Leisenring; Jorge Llop-Sayson; Marie Ygouf; et al. (The Astrophysical Journal, 2023)
The Y-dwarf WISE 1828+2650 is one of the coldest known brown dwarfs with an effective temperature of ∼300 K. Located at a distance of just 10 pc, previous model-based estimates suggest WISE1828+2650 has a mass of ∼5–10 M _J , making it a valuable laboratory for understanding the formation, evolution, and physical characteristics of gas giant planets. However, previous photometry and spectroscopy have presented a puzzle, with the near impossibility of simultaneously fitting both the short- (0.9–2.0 μ m) and long-wavelength (3–5 μ m) data. A potential solution to this problem has been the suggestion that WISE 1828+2650 is a binary system whose composite spectrum might provide a better match to the data. Alternatively, new models being developed to fit JWST/NIRSpec, and MIRI spectroscopy might provide new insights. This article describes JWST/NIRCam observations of WISE 1828+2650 in six filters to address the binarity question and to provide new photometry to be used in model fitting. We also report adaptive optics imaging with the Keck I0 m telescope. We find no evidence for multiplicity for a companion beyond 0.5 au with either JWST or Keck. Companion articles will present low- and high-resolution spectra of WISE 1828 obtained with both NIRSpec and MIRI.